1998
DOI: 10.1021/la970923g
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Kinetics of C10E8 at the Air−Water Interface

Abstract: The adsorption of C10E8 onto a clean air−water interface and the desorption out of an overcrowded interface due to a sudden shrinkage of a pendant bubble in a quiescent surfactant solution are studied. Video-enhanced pendant bubble tensiometry is employed for the measurement of the relaxation in surface tension. Relaxation profiles of surface tension for C10E8 molecules absorbing onto a freshly created air−water interface and desorbing out of a compressed air−water interface are obtained. The adsorption of C10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
109
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(123 citation statements)
references
References 21 publications
11
109
3
Order By: Relevance
“…1 and 2 for a broad range of n C (13,16,17). For some compounds, data from different authors are presented, which are in good mutual agreement.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…1 and 2 for a broad range of n C (13,16,17). For some compounds, data from different authors are presented, which are in good mutual agreement.…”
Section: Resultsmentioning
confidence: 57%
“…This tendency is observed also with an increasing number of oxyethylene groups in the C n EO m molecule. The experimental surface pressure isotherms of C n EO m for various m and fixed n (n = 10 and n = 12, respectively) obtained in (13,14,(16)(17)(18)(19)(20)(21) are shown in Figs. 3 and 4.…”
Section: Fig 2 the Same As Inmentioning
confidence: 99%
“…However, asymptotic solutions at long and at short times were obtained and have been successfully applied to surfactants (33). In particular, for ionic surfactants the equations in the form of derivatives are the following where D represents diffusion: [2] [ 3] If pure Fickian diffusion is the only mechanism for mass transport to the interface, one finds D short = D long = D, whereas activated diffusion may be taken into account by an effective diffusion coefficient D eff . Liggieri et al (34,35) introduced this idea, and their calculations showed that at long times small barriers have significant effects on Γ(t ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Lin et al (30,31) in studies on polyoxyethylene alcohols in air/water systems concluded that the controlling mechanism for mass transfer can change from diffusion to mixed kinetic-diffusion control as a function of bulk concentration. By examining how D changes with concentration they suggested a diffusion-controlled mechanism at dilute bulk concentrations, where the equilibrium surface coverage is low, and a mixed kinetic-diffusion control as the bulk concentration becomes higher and the equilibrium surface coverage is increased.…”
Section: Dynamic Interfacial Tensionmentioning
confidence: 99%